EKSPLORASI SENTIMEN PENGGUNA X TERHADAP ISU KESEHATAN MENTAL BERBASIS MACHINE LEARNING - Rifaldi, Dianda; Famuji, Tri Stiyo; Fanani, Galih Pramuja Inngam; Ramadhan, Fauzan Purma; Mulyadi, Iriene Putri; Saputra, Vanji (Department of Information System Muhammadiyah University of Riau, 2025)
Mental health has become an increasingly relevant topic in the digital era, particularly on social media platforms such as X, which serve as public spaces for expressing opinions and sharing personal experiences. This study aims to analyze public sentiment toward mental health topics on Twitter using the Multinomial Naive Bayes algorithm. Data were collected from tweets containing mental health-related keywords and processed through text cleaning and feature extraction using the TF-IDF method. The classification results showed that the model achieved an accuracy of 71%, with stronger performance in identifying negative sentiment compared to positive sentiment. A WordCloud visualization also revealed the frequent appearance of terms such as “mental,” “health,” “self,” and “disorder,” reflecting the main focus of online discussions. These findings indicate that machine learning-based sentiment analysis is effective in capturing public perceptions of mental health issues on social media. This research is expected to contribute to the development of digital communication strategies and real-time monitoring of psychosocial issues in online spaces.